Service Quality of domestic airlines in the face of COVID-19 in Nepal - Biswakarma, Dr Gangaram; Gnawali, Achyut (International Journal of Scientific Research and Management (IJSRM), 2021)
The coronavirus pandemic has turned the aviation industry on its head, transforming the passenger experience drastically. The airlines have faced significant challenges due to both the Covid-19 pandemic, the sequence of lockdowns and the provisions of safety and security legislation. There is more concern about the growing feeling that passengers are aware of the level of service. Airlines not only need to focus on service quality in today's highly competitive air transport environment, but also need to focus more on safety and security issues, especially at the time of the Covid-19 pandemic. The research related to these dimensional studies becomes more important in the COVID-19 scenario. Therefore, the objective of this study was to examine the impact of service quality dimensions on the overall quality of service of domestic airlines in Nepal in the midst of the Covid-19 pandemic. A quantitative methodology with a descriptive and explanatory research design was adopted in the study. A sample of 200 passengers recently travelling after the lockdown and reopening of the domestic airline service has been contacted. Out of which 160 responded to the questionnaire. In the sense of COVID-19 post lockdown operations, the service quality of domestic airlines is affected by various factors. All the likely factors that influence the quality of airlines need to be considered by airlines. Reliability, assurance, tangibility, empathy, and responsiveness are the variables. All these aspects play an important role in providing passengers with a reliable service. The dimensions of reliability, tangibility and responsiveness need to concentrate more on having the standard of service as desired in the sense of COVID-19 by domestic airlines in Nepal. It means that during COVID-19 and similar situations, tangibility must concentrate on the highest level of operation.